PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA PADA MATA KULIAH PEMBELAJARAN MIKRO JURUSAN PKK FT UNM - LILIS, LILIS; AISYAH, ST.; HUDIAH, ANDI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2024)
This research is a quantitative study with the following objectives: (1) To describe the Blended Learning Model for students of the PKK Department in the Microteaching course at the Faculty of Engineering, UNM; (2) To identify the learning motivation of PKK Department students using the Blended Learning Model in the Microteaching course at the Faculty of Engineering, UNM; (3) To examine the influence of the Blended Learning Model on the learning motivation of PKK Department students in the Microteaching course at the Faculty of Engineering, UNM. This study uses an ex-post facto research design. The research population consists of 101 undergraduate students of Fashion Design, PKK Department, Faculty of Engineering, UNM, from the 2021 cohort. The sample size is 50 students, determined using the Slovin formula. The data collection techniques employed include observation, documentation, and questionnaires (surveys). Data analysis techniques include descriptive analysis and simple regression analysis. The results of the study show that: (1) The description of the blended learning model for students falls into the "very high" category at 81.87%, as most students support the blended learning model for enhancing learning motivation; (2) The description of students' learning motivation falls into the "very high" category at 83.12%, indicating that various factors, both extrinsic and intrinsic, influence students' motivation to learn; (3) The influence of the blended learning model on students' learning motivation is "very high" and significant, with an impact of 81.6% between the variables, while 18.4% is influenced by other factors not examined in this study. ABSTRAKPenelitian ini merupakan penelitian kuantitatif dengan tujuan untuk mengetahui: (1) Gambaran Model Pembelajaran Blended Learning Mahasiswa Jurusan PKK pada mata kuliah Pembelajaran Mikro FT UNM; (2) Motivasi Belajar Mahasiswa Jurusan PKK Menggunakan Model Pembelajaran Blended Learning pada mata kuliah Pembelajaran Mikro FT UNM; (3) Pengaruh Model Pembelajaran Blended Learning terhadap Motivasi Belajar mahasiswa Jurusan PKK pada mata kuliah Pembelajaran Mikro FT UNM. Jenis peneilitian yang digunakan adalah ex-post facto. Populasi penelitian ini adalah Mahasiswa S1 Tata busana PKK FT UNM angkatan 2021 sebanyak 101 orang. Jumlah sampel adalah 50 Mahasiswa yang diperoleh menggunakan rumus slovin. Teknik pengumpulan data yang digunakan adalah observasi, dokumentasi dan kuesioner (angket). Teknik analisis data menggunakan analisis deskriptif dan analisis regresi sederhana. Hasil penelitian menunjukkan bahwa: (1) gambaran model pembelajaran blended learning mahasiswa berada pada kategori sangat tinggi sebesar 81,87%, dikarenakan rata-rata mahasiswa mendukung model pembelajaran blended learning untuk meningkatkan motivasi belajar; (2) gambaran motivasi belajar mahasiswa berada pada kategori sangat tinggi yaitu 83,12%, menunjukkan bahwa berbagai factor motivasi belajar dalam pengaruhnya terhadap keinginan mahasiswa baik itu secara ekstrinsik dan intrinsik; (3) Pengaruh model pembelajaran blended learning terhadap motivasi belajar mahasiswa berada pada kategori sangat tinggi dan signifikan dengan pengaruh sebesar 81,6 % antar variabel dan  dipengaruhi oleh faktor lain yang tidak diteliti.